Influence of Corruption Perception and Quality of Fiskus Service on The Compliance of Private Taxpayers - Aris Trismayadi Nurizki; Efi Tajuroh Afiah; Surachman Surachman (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
This study aims to determine the impact of the perception of corruption and the quality of service tax authorities either jointly or partially on the compliance of individual taxpayers in the Tax Office Primary Cilegon. This study categorized the type of quantitative descriptive with 100 respondents private persons registered in the Tax Office Primary Cilegon as samples and used the incidental sampling method. The results showed that the perception of corruption significantly influences adherence to an individual taxpayer (H1), the Quality of Service tax authorities' significant effect on compliance with an individual taxpayer (H2), the perception of corruption and the quality of service tax authorities jointly significant effect on tax compliance people private (H3)